The effects of the application of dynamic and PNF stretching on the explosive strength abilities of the lower limbs in warm-up in hockey and football athletes - Kabešová, Hana; Kabešová, Jitka; Tarantová, Nicole; Heidler, Josef; Černá, Lenka (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. This article deals with the issue of the effects of stretching on the level of explosive strength abilities in the lower limbs in warm-up. We know from a large amount of scientific studies that dynamic stretching has a positive effect on most sport performances (especially power and speed sports) rather than static stretching. Dynamically stretched muscles produce more power primarily because of the increased activation of the motor units. Higher performance during fast dynamic exercise is related to higher activation of the central nervous system. Proprioceptive neuromuscular facilitation (PNF) seems to bean optimal method of stretching when trying to increase joint mobility in the joint-muscle unit, where muscle contraction is used, followed by a relaxation phase and the subsequent stretching of the muscle. Aim of Study. The aim of this study is to compare the impact of dynamic and PNF stretching on explosive strength abilities of the lower limbs in active hockey players (n = 19, weight 84.7 ± 6.4 kg, height 179.8 ± 3.1 cm) and football (soccer) players (n = 23, weight 77.6 ± 5.1 kg, height 175.5 ±4.3 cm) ranging in age from 18 to 26. Material and Methods. The PNF method of Sölveborn was used, a method characterized by the physiological knowledge that a muscle significantly decreases its tone after isometric contraction is applied. This was compared in our research to the use of dynamic stretching during warmup. We used the following motor exams for testing the explosive strength of the lower limbs – a standing long jump (rebound with feet together) and a vertical jump (Sargent test). Results. We can state from the results of the parametric t-test that on the chosen level of significance (p < 0.05) practically significant differences were noted in the application of dynamic and PNF stretching in the hockey players’ vertical jump, and in addition to this, that the observed differences were substantively significant. For soccer players there are no statistically different results in the vertical jump test (p < 0.05) and that the participants have similar results after both dynamic and PNF stretching exercises. Conclusions. The impact of the acute application of dynamic stretching on explosive strength abilities in the lower limbs of hockey players was significantly more effective than the application of the PNF stretching technique in the vertical jump test performances. The experiment confirmed the short-term effect of the application of dynamic stretching on the explosive strength of the lower limbs of hockey players.
Keywords: stretching methods; muscle stretching exercises; explosive strength